Changes in each retinal layer and ellipsoid zone recovery after full-thickness macular hole surgery - Min-Woo Lee (Nature Portfolio, 2021)
Abstract To analyze the changes in each retinal layer and the recovery of the ellipsoid zone (EZ) after full-thickness macular hole (FTMH) surgery. Patients who underwent surgery for FTMH were included. Spectral-domain optical coherence tomography (SD-OCT) was performed preoperatively and postoperatively at 1, 3, 6, 9, and 12 months. A total of 32 eyes were enrolled. Ganglion cell layer, inner plexiform layer, and inner nuclear layer showed significant reductions over time after surgery (P = 0.020, P = 0.001, and P = 0.001, respectively), but were significantly thicker than those of fellow eyes at 12 months postoperatively. The average recovery duration of the external limiting membrane (ELM), outer nuclear layer (ONL), and EZ was 1.5, 2.1, and 6.1 months, respectively. Baseline best-corrected visual acuity (BCVA) (P = 0.003), minimum linear diameter (MLD) (P = 0.025), recovery of EZ (P = 0.008), and IRL thickness (P < 0.001) were significant factors associated with changes in the BCVA. Additionally, axial length (P < 0.001), MLD (P = 0.020), and IRL thickness (P = 0.001) showed significant results associated with EZ recovery. The IRL gradually became thinner after FTMH surgery but was still thicker than that of the fellow eye at 12 months postoperatively. The recovery of ELM and ONL may be a prerequisite for the EZ recovery. The BCVA change was affected by baseline BCVA, MLD, recovery of EZ, and IRL thickness. Additionally, axial length, MLD, and IRL thickness were significantly associated with EZ recovery.